Acyclovir Nephrotoxicity: A Case Report Highlighting the Importance of Prevention, Detection, and Treatment of Acyclovir-Induced Nephropathy - Raymond Fleischer; Michael Johnson (Case Reports in Medicine, 2010)
Acute kidney injury is an unfortunate complication of acyclovir therapy secondary to crystal-induced nephropathy. It is characterized by a decrease in renal function that develops within 24–48 hours of acyclovir administration indicated by a rapid rise in the serum creatinine. Failure to quickly realize this as an etiology of acute kidney injury can lead to excessive morbidity to the patient. The case described in this vignette is an example of the clinical manifestation of acyclovir crystal obstructive nephrotoxicity. We will briefly discuss the pathophysiology, diagnosis, prevention, and management of patients that present with acyclovir nephrotoxicity.